2012
DOI: 10.1007/978-3-642-31561-9_36
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Two Reference Estimation Methods in EEG Recording

Abstract: In [1] we proposed two methods to identify the reference electrode signal under the key assumption that the reference signal is independent from EEG sources. This assumption is shown to be possibly true for intracranial EEG with a scalp reference. In this paper, we theoretically prove that the obtained reference signal by using the second method in [1] or the equivalent MPDR approach [2] outperforms the widely used average reference (AR) if the real reference is independent from EEG sources. The simulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Moreover, we showed that SEPs were altered for both median and ulnar nerves, the later seldom tested when studying SEPs. The differences compared to previous studies, in terms of proportion of patients with altered SEPs (60 % in the present group, reaching 80 % when coupling with spinal diffusion MRI; Iglesias et al, 2015), could be explained by i) the extracephalic reference (ear lobe) we used, which is free from EEG distortions (Stephenson and Gibbs, 1951;Facco et al, 1989;Essl and Rappelsberger, 1998;Hu et al, 2012), and ii), EEG normalization (to 2 x SD pre-stimulus activity), which avoids any bias due to recording conditions that is known to influence the inter-and intra-individual comparisons of electrophysiological recordings (Iglesias et al, 2015). Moreover, our recordings indicate that the cortical background activity was similar in both groups, which may have also influenced the results of previous studies (Arieli et al, 1996;Klistorner and Graham, 2001;You et al, 2012).…”
Section: Sep Alteration In Alscontrasting
confidence: 79%
“…Moreover, we showed that SEPs were altered for both median and ulnar nerves, the later seldom tested when studying SEPs. The differences compared to previous studies, in terms of proportion of patients with altered SEPs (60 % in the present group, reaching 80 % when coupling with spinal diffusion MRI; Iglesias et al, 2015), could be explained by i) the extracephalic reference (ear lobe) we used, which is free from EEG distortions (Stephenson and Gibbs, 1951;Facco et al, 1989;Essl and Rappelsberger, 1998;Hu et al, 2012), and ii), EEG normalization (to 2 x SD pre-stimulus activity), which avoids any bias due to recording conditions that is known to influence the inter-and intra-individual comparisons of electrophysiological recordings (Iglesias et al, 2015). Moreover, our recordings indicate that the cortical background activity was similar in both groups, which may have also influenced the results of previous studies (Arieli et al, 1996;Klistorner and Graham, 2001;You et al, 2012).…”
Section: Sep Alteration In Alscontrasting
confidence: 79%
“…Most studies are concerned with general characteristics of the problem and discuss the views of previous authors and present new mathematical methods for the calculation of virtual reference electrodes that rather have theoretical research value than the actual use and verification in real practice. They propose methods and compare them with other analogs and selected actual reference electrodes, mostly with AR, or rarely A12 [10,11,20,27,32] using simulation signals and selected EEG records.…”
Section: Discussionmentioning
confidence: 99%
“…The results are illustrated by examples of EEG records, amplitude or power spectra, and topographic maps, which in turn are compared and evaluated on the basis of visual inspection with a purely qualitative verbal assessments and conclusions [2,4,10,11,21,22,29,30]. Some studies implement quantitative assessment of correlations, mean values, signal/noise ratios and illustrate them with timeline charts, scattering diagrams, and bar charts with standard errors [6,33] also discussed mainly with qualitative assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such procedures include ones based upon blind source separation (BSS), constrained BSS, and minimum power directionless response (MPDR) beam-forming (Madhu et al, 2012; Ranta and Madhu, 2012; Hu et al, 2012). Consistent with these procedures, we propose a method of reference effect mitigation developed from an application of statistical ideas – namely robust statistical estimation, rather than solely physical considerations.…”
Section: Introductionmentioning
confidence: 99%